2021
DOI: 10.15252/embr.202052196
|View full text |Cite
|
Sign up to set email alerts
|

ARHGAP45 controls naïve T‐ and B‐cell entry into lymph nodes and T‐cell progenitor thymus seeding

Abstract: T and B cells continually recirculate between blood and secondary lymphoid organs. To promote their trans‐endothelial migration (TEM), chemokine receptors control the activity of RHO family small GTPases in part via GTPase‐activating proteins (GAPs). T and B cells express several RHO‐GAPs, the function of most of which remains unknown. The ARHGAP45 GAP is predominantly expressed in hematopoietic cells. To define its in vivo function, we describe two mouse models where ARHGAP45 is ablated systemically or select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…This CpG in chromosome 19 is annotated to the ARHGAP45 gene, which has a circadian expression profile ( http://circadb.hogeneschlab.org/human , last accessed 2021/06/22). ARHGAP45 codes for a precursor of the histocompatibility antigen HA-1 and a GTPase activator for the Rho-type GTPases ( https://www.genecards.org/cgi-bin/carddisp.pl?gene=ARHGAP45&keywords=hmha1 , last accessed 2021/06/09) and has been linked to endothelial integrity and immune cell maturation [ 48 , 49 ]. In a previous study investigating the associations between DNA co-methylation modules and sleep in one of the cohorts included in this meta-analysis, namely Generation R, authors reported that a module containing a CpG located at ARHGAP27 was associated with actigraphy-assessed sleep duration [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…This CpG in chromosome 19 is annotated to the ARHGAP45 gene, which has a circadian expression profile ( http://circadb.hogeneschlab.org/human , last accessed 2021/06/22). ARHGAP45 codes for a precursor of the histocompatibility antigen HA-1 and a GTPase activator for the Rho-type GTPases ( https://www.genecards.org/cgi-bin/carddisp.pl?gene=ARHGAP45&keywords=hmha1 , last accessed 2021/06/09) and has been linked to endothelial integrity and immune cell maturation [ 48 , 49 ]. In a previous study investigating the associations between DNA co-methylation modules and sleep in one of the cohorts included in this meta-analysis, namely Generation R, authors reported that a module containing a CpG located at ARHGAP27 was associated with actigraphy-assessed sleep duration [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…MSTRG.207040.2 targets ABCA7 and ARHGAP45 ( Figure 5 ). It has been reported that ABCA7 haplodeficiency disturbs microglial immune responses in the mouse brain, and that ARHGAP45 controls naïve T- and B- cell entry into lymph nodes and T cell progenitor thymus seeding ( 55 ). FcγR triggers inflammatory reactions in response to antigen-antibody complexes.…”
Section: Discussionmentioning
confidence: 99%
“…5 ). It has been reported that ABCA7 haplodeficiency disturbs microglial immune responses in the mouse brain, and that ARHGAP45 controls naïve T- and B-cell entry into lymph nodes and T cell progenitor thymus seeding (50). FcγR triggers inflammatory reactions in response to antigen-antibody complexes.…”
Section: Discussionmentioning
confidence: 99%